Deletion of NAD(P)H:quinone oxidoreductase 1 represses Mre11-Rad50-Nbs1 complex protein expression in cisplatin-induced nephrotoxicity. (22nd January 2016) - Kim, Young-Jung; Kim, Tae-Won; Park, So-Ra; Kim, Hyun-Tae; Jung, Da-Young; Ryu, Si-Yun; Jung, Ju-Young
Highlights: MRN complex proteins and NQO1 were induced by cisplatin nephrotoxicity. Cisplatin-induced MRN complex protein expression decreased in NQO1-knockdown cells. Severe renal damage by cisplatin was followed by reduced MRN complex in NQO1 −/− mice. Cisplatin-injected NQO1 −/− mice showed disrupted DNA damage repair-related proteins. Reduced MRN complex might be related to the aggravated renal damage in NQO1 −/− mice. Abstract: The Mre11, Rad50, and Nbs1 (MRN) complex is a DNA double-strand break sensor involved in DNA damage repair. Herein, we explored whether deletion of NAD(P)H:quinone oxidoreductase 1 (NQO1), a cytoprotective gene, affected MRN complex expression in the kidney after cisplatin-induced acute kidney injury (AKI). In vitro, cisplatin increased the expression of MRN complex proteins and NQO1 in NQO1-expressing ACHN cells in a time- and concentration-dependent manner. The expression of MRN complex proteins was relatively inhibited in NQO1-knockdown cells. In vivo, increased expression of renal MRN complex proteins was accompanied by upregulation of γ-H2A histone member X, a DNA damage marker, in cisplatin-treated wild-type mice. Although the NQO1-knockout (NQO1 −/− ) mice showed more severe cisplatin-induced renal damage, the renal expression of MRN complex proteins was lower than in NQO1-expressing mice; expression of poly[ADP-ribose] polymerase 1, which promotes MRN complex accumulation, was also lower in these animals. In addition, cisplatin-induced expression of DNA damage repair-related proteins, ataxia telangiectasia mutated and sirtuin1, markedly decreased in the NQO1 −/− group, relative to the NQO1-expressing mice. These findings suggest that NQO1 deletion might be associated with decreased MRN complex expression, which might be partially responsible for the exacerbation of cisplatin-induced AKI in the absence of NQO1.